(untitled) - Proceedings of the international fisheries symposium-IFS 2012 (Ho Chi Minh, 2013)
Content: seed production and aquaculture systems; aquatic diseases and health management;animal nutrition and physiology; fisheries economics and management.
Keywords: Aquaculture,Nuôi trồng thuỷ sản,Freshwater fishes,Nuôi cá nước ngọt